Why is the Pack Persuasive? The Effect of Choice Status on Perceptions of Quality - Freda B. Lynn; Brent Simpson; Mark H. Walker; Colin Peterson (Sociological Science, 2016)
The logic of social proof and related arguments posits that decision makers interpret an actor’s sociometric position (such as popularity) as a signal for quality, especially when quality itself is difficult to ascertain. Although prior work shows that market-level behavioral patterns are consistent with this micro-level account, we seek to explicitly examine the extent to which (and the conditions under which) sociometric status information actually triggers assumptions about an actor’s underlying quality. We introduce two new web-based experiments to investigate how popularity impacts the selection of teammates. We find that the presence of popularity information creates a surprisingly robust quality halo around candidates in some situations but has no effect at all in others. Namely, consistent with Strang and Macy’s (2001) theory of adaptive emulation, choice status appears to affect quality perceptions as part of the rationalization for making attachments, but the halo disappears post-adoption. The implications of these results are discussed in the conclusion.